2020
DOI: 10.1038/s41467-019-13865-0
|View full text |Cite
|
Sign up to set email alerts
|

Low cost satellite constellations for nearly continuous global coverage

Abstract: Satellite services are fundamental to the global economy, and their design reflects a tradeoff between coverage and cost. Here, we report the discovery of two alternative 4-satellite constellations with 24- and 48-hour periods, both of which attain nearly continuous global coverage. The 4-satellite constellations harness energy from nonlinear orbital perturbation forces (e.g., Earth’s geopotential, gravitational effects of the sun and moon, and solar radiation pressure) to reduce their propellant and maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Resilience to unpredictable weather will also benefit from intercropping, with the creative arrangement of multiple interacting crop species to diversify the field and the landscape 101 , 172 , 285 , 286 . Sloat et al 287 reported that warming impact on maize, wheat and rice could be moderated by migration of these crops over time and the expansion of irrigation. Multiple-cropping systems and strategies to integrate animals and crops will make more efficient use of natural resources and applied inputs; these include systems such as permaculture, agroforestry, alley cropping, intercropping and sowing C 4 crops compared to C 3 crops.…”
Section: Adaptation Strategies In Response To Climate Changementioning
confidence: 99%
“…Resilience to unpredictable weather will also benefit from intercropping, with the creative arrangement of multiple interacting crop species to diversify the field and the landscape 101 , 172 , 285 , 286 . Sloat et al 287 reported that warming impact on maize, wheat and rice could be moderated by migration of these crops over time and the expansion of irrigation. Multiple-cropping systems and strategies to integrate animals and crops will make more efficient use of natural resources and applied inputs; these include systems such as permaculture, agroforestry, alley cropping, intercropping and sowing C 4 crops compared to C 3 crops.…”
Section: Adaptation Strategies In Response To Climate Changementioning
confidence: 99%
“…Moreover, their high operating costs are a burden on large-scale applications. In recent years, the dramatic drop in satellites' launching cost and the growing number of satellites in orbit significantly reduced the cost of highresolution satellite imagery [3]. Commercial satellite providers can offer high-resolution images (0.3 to 0.5 pixels/meter) with a daily and sub-daily revisiting frequency for most parts of the globe.…”
Section: Introductionmentioning
confidence: 99%
“…BNU-1 takes into account the balance between spatial resolution and revisit frequency, providing observations with finer spatial resolution than Terra/Aqua MODIS data and more revisit frequency than Landsat-8 OLI and Sentinel-2 MSI, benefiting the environmental monitoring of the polar regions. Also, the low cost of BNU-1 makes it financially feasible to construct a constellation observation system [12]. A five-satellite constellation system provides the ability to observe polar environmental elements on a daily basis with a spatial resolution finer than 100 m.…”
Section: Introductionmentioning
confidence: 99%
“…Both these models correct the errors of a satellite image by matching the CPs obtained from the target image (the image with geolocation errors) and the corresponding points from the reference image with high geolocation accuracy [17]. The parametric correction model corrects the errors by optimizing the inner and external orientation parameters in the geometric calibration model based on the differences between the CPs from the target and reference images [13,15,18], while the non-parametric model is performed by establishing the coordinates transformation model between coordinates of the target image and coordinates of the reference images based on the CPs [8,11,12].…”
Section: Introductionmentioning
confidence: 99%